Influence of aggregate gradation on the workability, mechanical properties and cost of steel fiber-reinforced concrete - Ulas, Merve Acikgenc; Alyamac, Kursat Esat; Ulucan, Zulfu Cinar (ASTM International, 2019)
Aggregate gradation is an essential concern in obtaining the intended properties in concrete production. The efficiency of this parameter dramatically increases for steel fiber-reinforced concrete (SFRC). Although steel fibers significantly improve the mechanical performance of concrete, they negatively affect the workability. Moreover, steel fibers, as expensive materials, drastically increase the cost of SFRC. For this reason, it is critical to correctly select the aggregate gradation and maximum aggregate size to be used in SFRC. In this study, the aim is to determine the effects of different aggregate gradations on the workability, mechanical performance, and cost of SFRCs. For this purpose, SFRC mixtures were produced with the maximum aggregate size of 16 and 31.5 mm. Vebe tests of fresh SFRCs were performed after the first mixing process and at the end of 30, 60, and 90-min intervals. The effects of test time and fine-to-coarse aggregate ratio on the workability were determined using response surface methodology. The compressive and flexural strengths and toughness performances of hardened SFRCs were also measured. In the last part of the study, to determine the effect of aggregate gradation on the cost, the unit costs of the SFRCs were calculated. The workability of SFRCs increased to a certain degree when finer aggregate gradation and smaller maximum aggregate size were preferred. Additionally, as finer aggregate gradation was used, it was observed that although the volume fraction of steel fibers did not change, the mechanical performance of SFRCs increased for a certain nominal aggregate size. Moreover, the unit cost of SFRCs decreased for a certain nominal aggregate size. As a result, by only selecting a finer aggregate gradation, it is possible to increase the workability and mechanical performance of SFRC and also produce more economic SFRCs for a constant volume fraction of steel fibers. Copyright © 2019 by ASTM International, 100 Barr Harbor Drive, PO Box C700, West Conshohocken, PA 19428-2959
Keywords: Flexural strength; Steel fiber-reinforced concrete; Toughness; Unit cost; Workability